The role of fermented foods in managing food allergies in children and adults: a systematic review - Hyseni, Bahtir; Papadimitriou, Konstantinos; Issa, Aline; Tonay, Ayşe Nur; Ergün, Burcu Gündüz; Gonzalez-Domenech, Carmen Maria; Arranz, Elena; Pula, Endra Luzha; Erem, Erenay; Garcia-Gutierrez, Enriqueta; Bouchaud, Gregory; Szajewska, Hania; et al. (Frontiers in Nutrition, 2026)
IntroductionFermented foods are among the oldest foods produced, and several different health benefits are attributed to their consumption even in the absence of concrete clinical evidence. To address this gap, this systematic review focuses on the effects of the consumption of fermented foods on food allergies.MethodsThis systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses and the relevant European Food Safety Authority guidelines. A systematic search strategy was established and registered in a study protocol in Open Science Framework. Scopus, MEDLINE, and Cochrane Library were searched with specific strings targeting human studies focusing on Fermented food and food allergies. Inclusion and exclusion criteria were defined based on the People Intervention Comparison Outcome elements. The Cadima tool was used to perform screening and selection of articles. A standard template was used for data extraction. Risk of bias assessment was performed using the Risk of Bias 2.0 Tool, Risk of Bias in Non-randomized Studies - of Interventions, or Newcastle–Ottawa Scale protocols. Additionally, a narrative section was written based on the European Food Safety Authority guidelines for the mechanism of action and product characteristics for evidence support.ResultsFrom a total of 558 initial records, 10 studies were finally selected. Fermented foods evaluated were fermented soy products, baked goods, fruit-based beverages, vinegar-treated foods, oat-based drinks, and dairy products (yogurt, cheese). In several studies, a reduced allergenicity was reported that was related to fermentation-mediated hydrolysis of allergenic proteins of gluten or soy. Additional mechanisms were related to anti-allergic immunomodulatory effects or favorable shifts in gut microbiota composition. In one case, fermented food consumption led to aggravation of the allergic response, presumably due to the compounds generated during soy fermentation. Risk of bias assessment revealed that most studies were performed with important methodological limitations.ConclusionWhile fermented foods hold promise in reducing food allergenicity and promoting tolerance, current evidence is limited to draw solid conclusions. Rigorous, well-designed human clinical trials, complemented by mechanistic studies in vitro and in vivo, are needed to clarify the role of fermented foods as dietary or even clinical tools to combat food allergies.Systematic review registrationhttps://osf.io/hgjaf/10.17605/OSF.IO/HGJAF.